The existence of complex transmission eigenvalues for spherically stratified media. Issue 1 (2nd January 2017) - Colton, David; Leung, Yuk-J.
Abstract : We continue our investigation of transmission eigenvalues for spherically stratified media. In particular, in the case when the index of refraction n ( r ) is such that, we establish conditions on n ( r ) to guarantee that there exists an infinite number of complex transmission eigenvalues and when, we establish very weak conditions on n ( r ) to guarantee the existence of complex transmission eigenvalues.